Identification of A*29:47, previously typed as A*29:19, in a Mexican bone marrow donor from the state of Hidalgo, Mexico. Issue 6 (3rd April 2013) - Alaez, C.; Munguía, A.; Flores, H.‐A.; Gorodezky, C.
Abstract : The A*29:47 allele was identified in a Mexican Mestizo unrelated bone marrow donor from the state of Hidalgo.